A Letter by Friar Aicardo da Camodea, Archbishop of Milan (28th of June 1319) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
The aim of this paper is to give a crital edition and to study a litterae patentes sent from Avignon by Aicardo of Camodeia, archibishop of Milan, to Obizzone of Momo, archibishop’s vicar. This missive is dated on 28th of June 1319 and it is kept at Berio Library in Genoa.
Keywords: Milan; archbishops; Aicardo da Camodeia; Berio Library in Genoa